Review on the fauna of Pterophoridae of the Republic of Guinea (Lepidoptera: Pterophoridae) - P. Ya. Ustjuzhanin; V. N. Kovtunovich; A. N. Streltzov (SHILAP, 2022)
The article gives a complete list of Pterophoridae species known from the Republic of Guinea. Three species, Exelastis crudipennis (Meyrick, 1932), Sphenarches erythrodactylus (Fletcher, 1911) and Hellinsia aethiopicus (Amsel, 1963) are reported for the fauna of this country for the first time.